Valoración del arraigo en prisiones preventivas tramitadas ante los juzgados de investigación preparatoria de Tarapoto - Ching Morante, Héctor (2018)
ABSTRACT In the present work, the assessment of the rooting in the preventive prisons processed before the courts of preparatory investigation of Tarapoto, during the year 2016 was investigated. Having as a general objective to determine how the appraisal of the arraigo is carried out in the preventive prisons processed before these courts, an observational guide was applied as well as a documentary analysis guide, using the inductive, deductive and analysis - synthesis methods, in turn exegetical and hermeneutics, and as a technique, documentary observation and documentary analysis were used. The main result was that most of the preventive custody proceedings are related to the crime of Illicit Drug Trafficking - TID, twenty three (23) of the forty (40) Preventive Prison Hearing Registry Acts collected on this matter , likewise the fiscal headquarters required preventive detention for a total of 58 people, of which preventive prison was imposed for 49 investigated, being that nine prosecuted did not fall this coercive measure. After the analysis and discussion of the results, it was concluded that there is appraisal of the rooting in preventive prisons processed before the Tarapoto Preparatory Investigation Courts during the year 2016, in accordance with the grounds supported by the procedural subjects who, in each preventive custody hearing, have sustained by means of oral, argumentative and persuasive skills the dimensions specified by the Supreme Court through Castion No. 631-2015-Arequipa establishing fundamental criteria for the determination of the rooting in judicial decisions, stating that, if there is a comprehensive motivation, and adequate argumentation in the hearing debate, the judge will be convinced of the need to impose this measure of coercion. The jurisdictional decision will not be based only on what is required by the prosecutor, but also by virtue of the work of the other procedural subjects participating in the hearing, whose abilities to oppose the tax requirement, will cause the Judge to analyze thoroughly if it is possible or not Impose preventive detention.